The Influence of International Divestment Experience on Re-entry Intentions - Hyötylä, Saida (fi=Turun yliopisto. Turun kauppakorkeakoulu|en=University of Turku. Turku School of Economics|, 2017)
The forward internationalization process of companies has been researched extensively. In contrast, there is considerably less research into the reduction in international business activities which is currently referred to as de-internationalization. However, after a company has experienced a reduction in its international business activities, it can always re-internationalize, that is increase its engagement in international markets. The degree of international engagement can be subject to fluctuations. Extant research posits that companies that re-internationalize are potentially able to benefit from their previous international experience, and have an advantage over newly internationalizing companies. Other research indicates that past experience influences a company’s internationalizing decisions. This paper is interested in exploring the connection between past international experience and re-entry intentions. This paper aims to create a better understanding of re-internationalization, and how past experience of international divestment influences the company’s perspective on re-engaging in international activities. This is accomplished through a case study on a company that is internationally active, but has at one point experienced a reduction in its international activities through a divestment in Poland. The company has never subsequently returned to the market. This paper uses the qualitative research approach with the particular method of a case study. The purpose is to create a holistic understanding of an under-researched phenomenon. The theoretical background of this work is comprised of theory on international divestment and re-internationalization. The research findings emanating from interviews with key personnel are analyzed against the theoretical background in order to deepen our understanding. The research findings indicate that past experience of international divestment has an influence on re-entry intentions, but this influence is only present with people who have first-hand knowledge and experience of the divestment. A person with direct experience of a negative event is more cautious in considering potential re-entry. However, this influence no longer exists with managers who do not have experience of the divestment. These findings confirm that previous experience and its influence is likely to become less relevant with management changes in the company.